Results of a national multicenter audit assessment of gynecologic history in surgical patients. Issue 2 (31st August 2017) - Wilson, Michael S.J.; Powell‐Bowns, Matilda; Robertson, Andrew G.; Luhmann, Andreas; Richards, Colin H.; ,
Abstract: Objective: To determine the adequacy of assessing gynecologic history for females of reproductive age (FRA) admitted to a general surgery department. Methods: The present prospective multicenter audit included FRA who were admitted for elective or emergency procedures to general surgery departments in Scotland between May 11 and May 25, 2015. Data were compared between patients who were admitted for elective and emergency treatment. Results: There were 530 FRA included from 18 centers, including 169 (31.9%) and 361 (68.1%) elective and emergency admissions, respectively. The date of last menstrual period was document for 203 (38.3%) patients, use of contraception for 149 (28.1%), sexual activity for 83 (15.7%), pregnancy status for 274 (51.7%), and the possibility of pregnancy for 237 (44.7%). A higher incidence of documented date of last menstrual period ( P= 0.002) and pregnancy status ( P< 0.001) were identified among emergency admissions, and the possibility of pregnancy was documented more commonly among elective admissions ( P< 0.001). Conclusions: Key factors required for gynecologic assessment were often not documented for FRA admitted to general surgery both as elective and emergency admissions. Surgical teams and medical undergraduates require educating regarding the importance of obtaining gynecologic history for all FRA. Abstract : The documentation of key elements of gynecologic history was inadequate for females of reproductive age admitted to general surgery as both elective and emergency patients.